The impact of two commonly used neutralizing agents in water sampling bottles on legionella and pseudomonas bacteria recovery. (November 2021) - Lai, S.; Nielsen, B.; Andrews, N.; Thompson, K.C.
Summary: Background: Microbiological monitoring may be indicated by the local risk assessment of hospital water systems. When water sampling is carried out, it is imperative that the activity of any residual biocide is completely neutralized. Sodium thiosulphate pentahydrate (Na₂S₂O₃·5H₂O) is commonly used to neutralize oxidizing biocides in water samples for microbiological testing. Ethylenediaminetetraacetic acid dihydrate (Na2 EDTA.2H2 O) is recommended to neutralize silver–copper ionization treated water samples. However, there are inconsistencies in the recommended effective concentration. Furthermore, sampling bottles dosed with Na2 EDTA.2H2 O are not commercially available. Aim: To investigate the efficacy of Na2 EDTA.2H2 O as a neutralizing agent compared with sodium thiosulphate (Na₂S₂O₃·5H₂O) on water samples treated with silver and copper ions and to assess the biocidal activity in water samples. Methods: An interlaboratory investigation was carried out using simulated water samples spiked with Legionella pneumophila or Pseudomonas aeruginosa with and without silver and copper ions. Bacterial recovery was determined in sterile sampling bottles dosed with either 50 mg/L Na2 EDTA.2H2 O or 180 mg/L Na₂S₂O₃·5H₂O as the chemical biocide neutralizing agent. Findings: Na₂S₂O₃·5H₂O effectively complexed both silver and copper ions and inhibited biocidal activity. The 50 mg/L of Na2 EDTA.2H2 O continued to demonstrate significant biocidal activity in the spiked samples. Conclusion: This study demonstrated that Na2 EDTA.2H2 O is not an efficacious neutralizing agent on water samples treated with silver and copper ions. Sample bottles dosed with 180 mg/L Na₂S₂O₃·5H₂O were more effective in neutralizing silver and copper ions generated in water that had been treated by silver–copper ionization systems.